BRAF‐Mutated Pleomorphic Xanthoastrocytoma is Associated with Temporal Location, Reticulin Fiber Deposition and CD34 Expression. (29th January 2014) - Koelsche, Christian; Sahm, Felix; Wöhrer, Adelheid; Jeibmann, Astrid; Schittenhelm, Jens; Kohlhof, Patricia; Preusser, Matthias; Romeike, Bernd; Dohmen‐Scheufler, Hildegard; Hartmann, Christian; Mittelbronn, Michel; Becker, Albert; et al.
Abstract BRAF V600E mutation and homozygous deletion of CDKN2A (p16) are frequent molecular alterations in pleomorphic xanthoastrocytomas (PXAs). We investigated 49 PXAs for clinical, histological and immunohistochemical characteristics related to BRAF mutation status. BRAF mutation was detected by immunohistochemical assay and DNA sequencing in 38/49 (78%) tumors. All but one PXA located in the temporal lobe harbored a BRAF V600E mutation (23/24; 96%) compared with 10/19 nontemporal PXAs (53%; P = 0.0009). Histological and immunohistochemical analysis demonstrated increased reticulin deposition (76% vs. 27%; P = 0.003) and a more frequent expression of CD34 in BRAF‐mutant PXAs (76% vs. 27%; P = 0.003). We further investigated the utility of combined BRAF V600E (VE1) and p16 analysis by immunohistochemistry to distinguish PXAs from relevant histological mimics like giant‐cell glioblastoma. Among PXAs, 38/49 (78%) were VE1‐positive, and 30/49 (61%) had a loss of p16 expression. The combined features (VE1 positivity/p16 loss) were observed in 25/49 PXAs (51%) but were not observed in giant‐cell glioblastoma (VE1 0/28, p16 loss 14/28). We demonstrate that temporal location, reticulin deposition and CD34 expression are associated with BRAF mutation in PXA. Combined VE1 positivity and p16 loss represents a frequent immunoprofile of PXA and may therefore constitute an additional diagnostic tool for its differential diagnosis.